Process Evaluation through Satisfaction Indices: Drawing Corollaries from National Agricultural Higher Education Project - Tripathi, Hema; Kaur, Sandeep; Agrawal, R C (Indian Journal of Extension Education, 2024)
Agriculture education has become an alluring opportunity for students and university faculty, because of NAHEP’s comprehensive vision to support SAUs and Deemed universities of the ICAR in providing more relevant and higher-quality education. Students and faculty availed benefits of the project and improved their skill set. Assessing student and faculty satisfaction was necessary to understand their level of contentment with the project’s activities and to establish a quantifiable measure of how effectively the project met their needs. Data was collected from 9322 students and 3386 faculty using Google Forms and analyzed by calculating average and weighted satisfaction score. The results depicted that in the case of student satisfaction index ratings, there was an increase of 6.6 per cent with a weighted satisfaction score of 2.42 in 2022-23 in comparison to the year 2020-21 with a weighted satisfaction score of 2.26. Faculty also revealed satisfaction with an increase of 3.8 per cent comprising a weighted satisfaction score of 2.61 in 2022-23 in comparison to the year 2020-21(2.51) highlighting the positive impact of the NAHEP program. Thus, the evaluation framework delved into intricate dynamics of the satisfaction levels of students and faculty and provided valuable insights into the efficacy of the project’s processes and outcomes.
Keywords: Students; Faculty; Satisfaction indices; Process evaluation; National Agricultural Higher Education Project